Perception of COVID-19 Pandemic by Brazilian People With Parkinson’s Disease and Multiple Sclerosis - Simieli, Lucas; Santinelli, Felipe B.; Costa, Elisa C.; Kuroda, Marina H.; Oliveira, Lorena R.; Penedo, Tiago; Pilon, Julia; Silveira, Aline P. B.; Assis, Iramaia S. A.; Tardelli, Erica; Okamoto, Erika; Barbieri, Fabio A. (Frontiers in Psychology, 2022)
COVID-19 in Brazil is threatening, and it has forced the government to adopt partial lockdown as a strategy to stop the spread of the virus at the beginning of the pandemic (March 2020). These preventive measures during the COVID-19 pandemic may affect the motor and non-motor symptoms in people with Parkinson’s disease (PD) and Multiple sclerosis (MS). Thus, the purpose of this study was to investigate the effects of the COVID-19 pandemic lockdown on the motor and non-motor symptoms, physical activity level, and quality of life, and sleep quality in Brazilian people with PD and MS. One hundred and fifty-three participants (PD-97 and MS-56) answered our survey to identify the perception and the effects of the COVID-19 pandemic on motor and non-motor symptoms, physical activity level, and quality of life and sleep. Our results indicated negative effects of motor and non-motor symptoms, mainly motor performance, bradykinesia, loneliness, and anxiety, and quality of life and sleep quality in Brazilian people with PD and MS during partial lockdown due to COVID-19 pandemic. Our results suggest that despite the preventive and security measures being necessary to avoid the collapse of the health system and to prevent infections and deaths, people with PD and MS require remote care to reduce the effects of isolation in motor and non-motor aspects of the diseases. Teleinterventions, such as home-based exercise, should be included in the new routine of people with PD and MS to reduce the impacts of lockdown and to maintain quality of life at a good level.